Evaluating Growth Indicators Among Infants Aged 6–24 Months: The Role of Complementary Feeding in Preventing Malnutrition - Preeti V. Patankar (The Bioscan, 2025)
This study evaluates the relationship between complementary feeding (CF) practices and growth indicators among infants aged 6 to 24 months in Pune City. Using a cross-sectional observational design, anthropometric measurements (height-for-age and weight-for-age) were collected and analyzed according to WHO Child Growth Standards (2006). Infants were categorized into three age groups and assessed for nutritional status using Z-scores. The findings indicate that a majority of infants, particularly in the 6–12 months group, fell within the normal growth range, while stunting and underweight were more evident among older infants, suggesting a decline in appropriate CF practices over time. Chi-square analysis revealed a significant association between timely, adequate CF and better growth outcomes. These results underscore the importance of early nutritional education and intervention to prevent malnutrition during infancy.